Pengaruh Kepemimpinan Transformasional dan Program Pelatihan dan Pengembangan Terhadap Kinerja Karyawan Melalui Kompetensi Di Petrochina Internasional Jabung Ltd - Gajianto Pangarso Hari Kuncoro; Sihol Situngkir; Syahmardi Yacob (Universitas Batanghari, 2021)
This study aims to examine whether there is an influence of transformational leadership and training and development programs on employee performance with the mediation variable, namely competence. Primary data source using a questionnaire taken on the research object at PetroChina International Jabung Ltd with a total sample of 144 respondents. The study uses quantitative descriptive analysis and data processed with SPSS 24 namely regression analysis and path analysis. The results showed that there was a positive influence on transformational leadership and training and development programs on employee performance. Transformational leadership and training and development programs affect on employee competencies. Employee competence mediates transformational leadership on employee performance and competence also mediates training and development programs on employee performance. The study recommends that the leaders of the PetroChina International Jabung Ltd Office need toreview the policies of improving the implementation of training and development programs and employee competencies so that employees can contribute more productively to the Office.